Atractylodes lancea Rhizoma Attenuates DSS-Induced Colitis by Regulating Intestinal Flora and Metabolites - Qu, Linghang; Liu, Chunlian; Ke, Chang; Zhan, Xin; Li, Lanqing; Xu, Haiying; Xu, Kang; Liu, Yanju (The American journal of Chinese medicine (1979), 2022)
(Thunb.) DC. is a herb widely used traditionally for the treatment of gastrointestinal diseases such as gastric ulcer, spleen deficiency, and diarrhea. In China, people fry raw (SCZ) together with wheat bran to make bran-fried (FCZ). Ancient Chinese texts have documented that FCZ can enhance the function of regulating the intestines and stomach. Nevertheless, the effect and mechanism of SCZ and FCZ on ulcerative colitis (UC) are still unclear. The aim of this study was to compare the therapeutic effects of SCZ and FCZ and their mechanisms on dextran sulfate sodium (DSS)-induced UC in mice. The chemical constituents of SCZ and FCZ were analyzed using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) with six reference compounds. The effects of SCZ and FCZ were investigated based on their effects on weight loss, disease activity index (DAI) score, colon length shortening, goblet cell loss, and pathological changes using the colons from a mouse model of DSS-induced UC. The effects of SCZ and FCZ on levels of the inflammatory cytokines (tumor necrosis factor-[Formula: see text], interleukin-6, interleukin-1[Formula: see text], mucoprotein (MUC2), tight protein (ZO-1, occludin), and the activation of macrophages were determined using immunohistochemistry (IHC) and immunofluorescence (IF). 16s RNA sequencing technology was used to detect the composition of the intestinal flora in each group. Nontargeted metabonomics was used to detect the serum metabolite levels of mice in each group. Pearson analysis was used to determine the correlation between the intestinal flora, metabolites, and pathological indices. Reverse transcription-polymerase chain reaction was used to detect the genes of different metabolite-related enzymes. A pseudogerm free (PGF) mouse model was used to verify whether the effect of SCZ and FCZ in UC depends on the regulation of intestinal flora. SCZ and FCZ could inhibit weight loss and decrease the DAI score, colon length shortening, goblet cell loss, and the extent of pathological changes in the colons of mice with DSS-induced colitis. Moreover, SCZ and FCZ inhibited the decrease in MUC2, ZO-1, occludin, production of pro-inflammatory factors, and activation of pro-inflammatory macrophages in colonic tissue. The effect of FCZ was better than that of SCZ. SCZ and FCZ not only inhibited the abundance of harmful bacteria and increased the abundance of beneficial bacteria, but also regulated the metabolism of disease-related metabolites such as amino acid and cholesterol metabolism. Both preparations inhibited the gene expression (Slc6A7, PRODH, Sdsl, HMGCR, SREBP-2) of different metabolite-related enzymes. In the PGF mouse model, the above effects were not observed. Rhizoma Atractylodes was effective in alleviating DSS-induced UC in mice, and FCZ was found to be superior to SCZ. The mechanism of action of FCZ and SCZ is mainly related to the regulation of intestinal flora and their associated metabolites.